2016
DOI: 10.6023/cjoc201509046
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Synthesis of Oxyresveratrol Catalyzed by Palladium

Abstract: A convenient method for the synthesis of oxyresveratrol catalyzed by palladium is described. 2,4-Dihydroxyiodobenzene underwent Heck reaction with acrylic acid, then decarboxylation, and further underwent Heck reaction with 3,5-dihydroxyiodobenzene, furnishing oxyresveratrol in a high yield. The title compound was characterized by MS and NMR. This synthetic method has several advantages such as less step processes, high yield, simple operations, and promises to be applied in industrial production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…2,4-Dihydroxyiodobenzene was allowed to react with acrylic acid under Heck reaction conditions (Pd catalyzed reaction) to provide an intermediate that, after decarboxylation and coupling with 3,5-dihydroxyiodobenzene through Heck reaction, yielded ORV (Figure 5) It is noteworthy that ORV is light-sensitive, as it was reported that this compound rapidly underwent a trans-cis-photoisomerization and photodegradation by UV irradiation in ethanol solution [137]. More recently, a simple two-step synthesis of ORV was reported [136]. 2,4-Dihydroxyiodobenzene was allowed to react with acrylic acid under Heck reaction conditions (Pd catalyzed reaction) to provide an intermediate that, after decarboxylation and coupling with 3,5-dihydroxyiodobenzene through Heck reaction, yielded ORV (Figure 5).…”
Section: Chemical Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…2,4-Dihydroxyiodobenzene was allowed to react with acrylic acid under Heck reaction conditions (Pd catalyzed reaction) to provide an intermediate that, after decarboxylation and coupling with 3,5-dihydroxyiodobenzene through Heck reaction, yielded ORV (Figure 5) It is noteworthy that ORV is light-sensitive, as it was reported that this compound rapidly underwent a trans-cis-photoisomerization and photodegradation by UV irradiation in ethanol solution [137]. More recently, a simple two-step synthesis of ORV was reported [136]. 2,4-Dihydroxyiodobenzene was allowed to react with acrylic acid under Heck reaction conditions (Pd catalyzed reaction) to provide an intermediate that, after decarboxylation and coupling with 3,5-dihydroxyiodobenzene through Heck reaction, yielded ORV (Figure 5).…”
Section: Chemical Synthesismentioning
confidence: 99%
“…2,4-Dihydroxyiodobenzene was allowed to react with acrylic acid under Heck reaction conditions (Pd catalyzed reaction) to provide an intermediate that, after decarboxylation and coupling with 3,5-dihydroxyiodobenzene through Heck reaction, yielded ORV (Figure 5). More recently, a simple two-step synthesis of ORV was reported [136]. 2,4-Dihydroxyiodobenzene was allowed to react with acrylic acid under Heck reaction conditions (Pd catalyzed reaction) to provide an intermediate that, after decarboxylation and coupling with 3,5-dihydroxyiodobenzene through Heck reaction, yielded ORV (Figure 5) It is noteworthy that ORV is light-sensitive, as it was reported that this compound rapidly underwent a trans-cis-photoisomerization and photodegradation by UV irradiation in ethanol solution [137].…”
Section: Chemical Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…However, efforts to synthesize 2 and its natural dimers, such as 3-6, 3 have been scarce in comparison with those for 1 and its oligomers. 4 Three routes are available for the construction of the trans-double bond in monomer 2: palladium-catalyzed Heck coupling, as reported by Li's group; 5 Perkin condensation, as conducted by Zou and co-workers, 6 or a Wittig reaction, as performed by Lee et al 7a and by Reimann. 7b Processes for the synthesis of the natural oligomers of 2 have been rarely reported, apart from an acid-catalyzed dimerization…”
mentioning
confidence: 99%